Review articleInsulin resistance and its consequences in chronic hepatitis C - Kukla, Michał; Piotrowski, Damian; Waluga, Marek; Hartleb, Marek (Clinical and Experimental Hepatology, 2015)
Chronic hepatitis C (CHC) is generally a slowly progressive disease, but some factors associated with rapid progression have been identified. Hepatitis C virus (HCV) may contribute to a broad spectrum of metabolic disturbances – namely, steatosis, insulin resistance (IR), increased prevalence of impaired glucose tolerance, type 2 diabetes mellitus (T2DM), lipid metabolism abnormalities and atherosclerosis. HCV can directly or indirectly cause both IR and steatosis, but it is still not resolved whether this viral impact bears the same prognostic value as the metabolic counterparts. As the population exposed to HCV ages, the morbidity due to this disease is increasing. The rising epidemic of obesity contributes to higher prevalence of IR and T2DM. Our understanding of the mutual association between both disease states continues to grow, but is still far from complete. This review briefly discusses the most probable mechanisms involved in IR development in the course of CHC. Molecular mechanisms for the direct and indirect influence of HCV on intracellular insulin signaling are described. Subsequently, the consequences of IR/T2DM for disease progression and management are summarized.